Арилизопреноиды в составе нефтей Нюрольской впадины (юго-восток Западной Сибири); Нефтехимия; Т. 57, № 1 - Чиркова Д. Ю. Диана Юрьевна; Красноярова Н. А. Наталья Алексеевна; Серебренникова О. В. Ольга Викторовна; Оленев Я. В. Ярослав Валерьевич (2017, 2017)
Заглавие с экрана